2009
DOI: 10.1007/s10201-009-0291-7
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Cladocera (Crustacea, Branchiopoda) in Lake Tonle Sap and its adjacent waters in Cambodia

Abstract: Sixty species of freshwater Cladocera (Crustacea, Branchiopoda) are recorded from Lake Tonle Sap and its adjacent waters, Cambodia. Four species, Ceriodaphnia laticaudata, Bunops cf. tuberculatus, Leydigia australis, and Chydorus cf. dentifer are newly recorded from Southeast Asia, and occurrence of Macrothrix pholpunthini is secondary confirmed in the world. The present cladoceran fauna is characterized by having rich epiphytic and benthic forms. It can be associated with the shallow and vegetation-rich habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Described from Syria (Richard, 1894) as Pleuroxus, then moved to a special genus Ephemeroporus (Frey, 1982b) and found to be tropicopolitan (Smirnov, 1996;Kotov et al, 2011. It is widely distributed in other SE Asian countries (Maiphae et al, , 2008Tanaka and Ohtaka, 2010;Korovchinsky, 2013a). Maiphae et al (2005Maiphae et al ( , 2008 identified three other species of the genus Ephemeroporus from Thailand, but all our populations were similar to Ephemeroporus barroisi.…”
Section: Ephemeroporus Frey 1982mentioning
confidence: 62%
See 3 more Smart Citations
“…Described from Syria (Richard, 1894) as Pleuroxus, then moved to a special genus Ephemeroporus (Frey, 1982b) and found to be tropicopolitan (Smirnov, 1996;Kotov et al, 2011. It is widely distributed in other SE Asian countries (Maiphae et al, , 2008Tanaka and Ohtaka, 2010;Korovchinsky, 2013a). Maiphae et al (2005Maiphae et al ( , 2008 identified three other species of the genus Ephemeroporus from Thailand, but all our populations were similar to Ephemeroporus barroisi.…”
Section: Ephemeroporus Frey 1982mentioning
confidence: 62%
“…Leydigiopsis sp. This is apparently a new taxon, rare yet occuring in different countries of the Oriental region (Sanoamuang, 1998;Maiphae et al, 2005;Tanaka and Ohtaka, 2010;). The species is described by Van Damme and Sinev (2013).…”
Section: Leydigia Kurz 1875mentioning
confidence: 97%
See 2 more Smart Citations
“…The faunistic composition of the group was re-evaluated for Thailand (Maiphae et al, , 2008 and local faunas were investigated in some regions of Thailand, Cambodia and Laos (Pholpunthin, 1997;Sanoamuang, 1998;Korovchinsky and Sanoamuang, 2008b;Tanaka and Ohtaka, 2010;Kotov et al, 2013). Several taxonomic groups were revised, and several new species were described Sanoamuang, 2008a, 2008b;Korovchinsky, 2011;Sanoamuang, 2004a, 2004b;Sinev, 2011Sinev, , 2012Sanoamuang, 2007, 2011;Sinev and Kotov, 2012;Van Damme and Sinev, 2013;.…”
Section: Introductionmentioning
confidence: 99%